High-temperature superconducting material-based full-lifetime evaluation method of offshore wind turbine - ZHANG TIANYANG; WANG XIAOWEI; WEI YANFANG; ZOU JIN; XIAO JIJUN; ZHENG ZHENG; XU XIAOZHUO (2016)
The invention discloses a high-temperature superconducting material-based full-lifetime evaluation method of an offshore wind turbine. The method comprises the steps of determining a full-lifetime evaluation period; limiting boundary conditions; determining asset allocation; setting offshore wind turbine parameters; building an evaluation index library; carrying out evaluation index sensitivity and uncertainty analysis; and determining comprehensive evaluation. The used high-temperature superconducting material is the second generation of high-temperature superconducting material; and a superconducting layer is manufactured by a thin-film vacuum deposition technology and comprises six layers in all, namely a copper bottom layer, a hastelloy alloy C276 layer, a yttrium barium copper oxide layer, a nano layer, a silver layer and a 20micron copper top layer separately. By the method, the key index of affecting the full-lifetime of the offshore wind turbine can be determined; management planning decision is facil